Development of Natural Tourism Objects in Kampar District (Case Study of Natural Bathing Tourism Objects in Pantai Cermin Village, Rumbio Jaya District, Kampar Regency) - Iskandar Iskandar; Putra Budi Ansori (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this study was to determine the development and attractiveness of the natural baths of Sulem flora in terms of developers and tourists, the factors that support and the impact of developing Sulem flora natural baths as a tourist destination in Kampar Regency. This study uses the theory of Social Practices from Bourdieu. This study uses a qualitative research method with a case study approach. Source of data from interviews with informants and related documents. The sampling technique used purposive sampling. Data collection techniques using observation, interviews and documentation. Data validity uses source triangulation. Data analysis using an interactive model. The results showed that the development of the Sulem Flora Natural Bath has improved the quality of tourism management and services, marked by an increase in the number of tourist visits to the Sulem Flora Natural Bath. The development of the Sulem Flora Natural Baths was also accompanied by the habitus of the people of Pantai Cermin Village from their participation as food selling tours in tourist areas, parking area managers, workers at the Sulem Flora Natural Baths by using economic capital, social capital, cultural capital and symbolic capital. The participation of the people of Pantai Cermin Village to develop tourism can be seen in the decisions they fought for and fought for in their area as a tourist area, in the production of practices that could support the development of the Flora Sulem Nature Bath and also in improving the welfare and quality of life of the community. local community.